Maximiano Rosales and Rafael Herrera Robinson. An odd pair in Mexican popular music - Ochoa Serrano, Alvaro (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2025)
The text addresses the biography and musical career of Maximiano Rosales (1868-1927) and Rafael Herrera Robinson (1866-1945), popular musicians born in Mexico City, interpreters of the Mexican popular lyric of the early twentieth century.